Management of Natural Resource Utilization in Realizing Adiwiyata Schools - Hasanah, Meita Siti; Khamidi, Amrozi; Karwanto, Karwanto (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe and analyze the management of natural resource utilization in realizing Adiwiyata Schools at SD Negeri Tunggalpager, Mojokerto Regency. The research used a qualitative approach focusing on planning, implementation, and evaluation processes. Data were collected through in-depth interviews, observations, and documentation involving the principal, teachers, students, and school documents. Data analysis applied the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing, while validity was ensured through source, time, and technique triangulation. The findings indicate that natural resource management has been integrated with Adiwiyata principles through environmental activities such as waste management, school gardening, efficient resource use, and environmentally friendly canteen practices. Program planning was conducted participatively, implementation emphasized practice-based learning, and evaluation was carried out continuously. Supporting factors include strong leadership commitment and active participation of the school community, while obstacles relate to limited facilities, funding, and time. The study concludes that systematic and collaborative management of natural resources effectively supports the realization of Adiwiyata Schools.